Experimental Research on Fatigue Behavior of Existing Reinforced Concrete Beams. (15th October 2020) - Qu, Guangzhen; Huang, Pingming; Zhou, Guangli; Lv, Sizhong
Abstract : In order to obtain the law of the fatigue damage development of reinforced concrete hollow beams that has been in service for 24 years, its solid hollow beams were removed and transported to the laboratory for loading test. Two beams were selected for static loading to obtain the ultimate flexural bearing capacity, and three beams were, respectively, subjected to constant-amplitude fatigue loading with different load amplitudes. The static and dynamic behaviors of the beams were monitored in the fatigue test. The fatigue failure of the beams showed that the outermost rebar at the butt weld fractured at first, and the crack width at the fracture position of the steel bar was about 0.3 mm, which was largest in all cracks. After a rebar was broken, midspan deflection and flexibility increased by approximately 20% and 10%, respectively, relative to the initial state. The damage developed rapidly in the following range: (1) the first 10, 000 fatigue cycles; (2) after fatigue fracture of the rebar; and in the intermediate stage of fatigue test, the damage development was relatively stable. As the loading amplitude increased, the stiffness degradation and the cumulative damage that occured under the same loading cycle were more significant.